ANALISIS UKURAN PERUSAHAAN DAN PERTUMBUHAN ASET TERHADAP STRUKTUR MODAL PERBANKAN UMUM PEMERINTAH DI BURSA EFEK INDONESIA - Lilianti, Emma (Fakultas Ekonomi Universitas IBA, 2017)
This study aims to determine the effect of firms and asset growth on capitalstructure government general banking in Indonesia Stock Exchange. The problem in thisresearch how to influence firm size and asset growth on capital structure governmentgeneral banking in BEI? Data analysis, autocorrelation, multicolinearity andheterocedasticity test. The population is the entire company government general bankingin BEI as many as 4 companies, with the selected sample of 4 companies through thesampling census. The results showed firm size and asset growth have influence on capitalstructure government general banking in Indonesia Stock Exchange (BEI).